Meta-cognitive strategies and nursing students' achievement - Salari, Mohsen; Ahmad Tarmizi, Rohani; Hamzah, Ramlah; Hambali, Zarida (International Foundation for Research and Development, 2013)
In the information era in which there is an increasing and rapid information change, education system needs to enable students to solve the problems of real world with their acquired skills. Meta-cognition is essential for successful learning and students can learn and use it to improve their performance. This paper was an attempt to investigate the reliability of meta-cognitive awareness inventory that is generated by Schraw and Dennison (1994) and its correlation with nursing students’ achievement in Iran. The design adopted for this study was a descriptive correlation design. To this end, 40 female university students majoring in nursing were selected as the sample. Pediatric nursing performance was measured using a test which included higher and lower order questions. The results indicated that (a) the questionnaire has acceptable internal consistency, with a Cronbach alpha coefficient of .74, (b) there was a strong, positive correlation between the two variables, r = .729, n = 40, p<0.01, with high levels of meta-cognitive awareness associated with higher levels of performance in course of pediatric nursing. In conclusion, meta-cognitive strategies may have impact on nursing performance among university students.